A study of character forms and uses in Chanmen niansong ji 禅门拈颂集. (June 2019) - Kim, Aeyoung
This study aims to examine the features of the characters in Chanmen niansong ji 禅门拈颂集, a central text, while paying special attention to the variant Chinese characters (different characters with a similar pronunciation or meaning) it contains. Since Chanmen niansong ji 禅门拈颂集 includes a variety of such characters, it is possible to trace a diversity of changes in character forms from Lishu 隶书 to Kaishu 楷书. For this purpose, this study will classify variant Chinese characters in Chanmen niansong ji 禅门拈颂集 using two different classification standards, namely the structure of these characters and the method of generating them. Both versions of Chanmen niansong ji 禅门拈颂集, the variant Chinese character version and the conventional version include wuzi 误字 (wrong character), yanzi 衍字 (meaninglessly added characters), and tongjiazi 通假字 (loan character). It was found that there were some differences in the form and structure of characters in the two versions of the text. It is expected that the results of this investigation will contribute to the hermeneutic reconstruction of Chanmen niansong ji 禅门拈颂集. It seems clear that Chanmen niansong ji 禅门拈颂集 was published during the Song 宋 Dynasty in China, that is, the early Gaoli 高丽 Dynasty, a period when Tripitaka Koreana was also engraved in Gaoli 高丽. Through a basic analysis, several differences between Chanmen niansong ji 禅门拈颂集, the conventional version, and the variant Chinese character version were found, in terms of the form of their variant Chinese characters. Future research will compare the forms of the variant characters in these two texts, focusing on the pattern of character forms in the Song 宋 Dynasty in China, which is the counterpart of the Gaoli 高丽 Dynasty in Korea. This will help produce more abundant data related to character form.